2000
DOI: 10.1074/jbc.m001854200
|View full text |Cite
|
Sign up to set email alerts
|

The FtsJ/RrmJ Heat Shock Protein of Escherichia coli Is a 23 S Ribosomal RNA Methyltransferase

Abstract: Ribosomal RNAs undergo several nucleotide modifications including methylation. We identify FtsJ, the first encoded protein of the ftsJ-hflB heat shock operon, as an Escherichia coli methyltransferase of the 23 S rRNA. The methylation reaction requires S-adenosylmethionine as donor of methyl groups, purified FtsJ or a S 150 supernatant from an FtsJ-producing strain, and ribosomes from an FtsJ-deficient strain. In vitro, FtsJ does not efficiently methylate ribosomes purified from a strain producing FtsJ, suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
130
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(133 citation statements)
references
References 32 publications
1
130
0
Order By: Relevance
“…We have previously suggested as one of a number of possibilities that the guide RNAs used in eukaryotes to identify the U residues destined for conversion to ⌿ might be RNA chaperones for the correct folding of ribosomal RNA (Ofengand & Fournier, 1998)+ In this view, ⌿ formation would be merely a signal that folding had occurred and it was time for the chaperone to dissociate, rather than having an intrinsic function+ If this view were extended to prokaryotes, substituting the synthases for guide RNAs, the ⌿ synthases might then be protein chaperones of RNA folding, helping in some as yet undefined way to achieve the correct structure+ However, it does not seem so likely that ⌿ formation is a necessary completion signal, as in its absence, when mutant RluD was used, complete growth rate restoration was observed (Table 2)+ More likely, RluD, and possibly the other synthases as well, have two distinct functions, one of which is related to the observed growth defects, and the other to ⌿ formation, the latter occurring for still unknown reasons+ There is some precedent for these ideas+ First, the methyltransferase that makes m 5 U54 in tRNA is indispensable in E. coli, yet its methylation activity is not required (Persson et al+, 1992)+ Second, Dim1p, the yeast enzyme which makes m 6 2 Am 6 2 A at the 39 end of the small subunit rRNA and is essential for the yeast cell (Lafontaine et al+, 1994), can dispense with its methylase activity (Lafontaine et al+, 1998)+ Third, two LSU rRNA 29-O-methyltransferases are known whose absence perturbs ribosome assembly and results in severe or lethal growth defects+ One is PET56, a yeast 29-O-methyltransferase specific for G2251 (E. coli numbering) in yeast mitochondria (Sirum-Connolly & Mason, 1993)+ The other is FtsJ, which makes Um2552 in E. coli (Bügl et al+, 2000;Caldas et al+, 2000aCaldas et al+, , 2000b)+ In the latter example, it is not known whether the 29-O-methylation is required for proper ribosome assembly, but in the former case, recent work has shown that rescue of ribosome assembly does not require methylation (T+ Mason, pers+ comm+)+ Thus, like RluD and TruB, the protein is needed but not the product of the reaction it catalyzes+ Inhibition of 50S subunit assembly in both Dust and Tiny RluD-minus strains has also recently been observed (L+ Peil, N+ Gutgsell, J+ Ofengand, & J+ Remme, unpubl+ results)+ Considering all these results, a pattern begins to emerge in which rRNA modifying enzymes, at least the most common ones, ⌿ synthases and 29-O-methyltransferases, may have an assembly function in their own right, independent of their catalytic role in modified base formation+ In this regard, it is interesting to note the amino acid sequence homology between the N-terminus of RluD (residues 19-49) of this 326 amino acid protein with residues 10-40 of Hsp15, a protein highly induced by heat shock (Korber et al+, 1999)+ Hsp15 is a 133 amino acid protein that consists almost entirely of a new type of RNA-binding fold and which binds to 50S subunits carrying nascent protein chains with nanomolar affinity + In this context, the occurrence of pseudorevertants should be noted+ Such second-site mutants are found readily in the Dust strain, and pains must be taken to avoid them during subculturing+ They occur much more rarely in the Tiny strain, possibly because the grow...…”
Section: Discussionmentioning
confidence: 99%
“…We have previously suggested as one of a number of possibilities that the guide RNAs used in eukaryotes to identify the U residues destined for conversion to ⌿ might be RNA chaperones for the correct folding of ribosomal RNA (Ofengand & Fournier, 1998)+ In this view, ⌿ formation would be merely a signal that folding had occurred and it was time for the chaperone to dissociate, rather than having an intrinsic function+ If this view were extended to prokaryotes, substituting the synthases for guide RNAs, the ⌿ synthases might then be protein chaperones of RNA folding, helping in some as yet undefined way to achieve the correct structure+ However, it does not seem so likely that ⌿ formation is a necessary completion signal, as in its absence, when mutant RluD was used, complete growth rate restoration was observed (Table 2)+ More likely, RluD, and possibly the other synthases as well, have two distinct functions, one of which is related to the observed growth defects, and the other to ⌿ formation, the latter occurring for still unknown reasons+ There is some precedent for these ideas+ First, the methyltransferase that makes m 5 U54 in tRNA is indispensable in E. coli, yet its methylation activity is not required (Persson et al+, 1992)+ Second, Dim1p, the yeast enzyme which makes m 6 2 Am 6 2 A at the 39 end of the small subunit rRNA and is essential for the yeast cell (Lafontaine et al+, 1994), can dispense with its methylase activity (Lafontaine et al+, 1998)+ Third, two LSU rRNA 29-O-methyltransferases are known whose absence perturbs ribosome assembly and results in severe or lethal growth defects+ One is PET56, a yeast 29-O-methyltransferase specific for G2251 (E. coli numbering) in yeast mitochondria (Sirum-Connolly & Mason, 1993)+ The other is FtsJ, which makes Um2552 in E. coli (Bügl et al+, 2000;Caldas et al+, 2000aCaldas et al+, , 2000b)+ In the latter example, it is not known whether the 29-O-methylation is required for proper ribosome assembly, but in the former case, recent work has shown that rescue of ribosome assembly does not require methylation (T+ Mason, pers+ comm+)+ Thus, like RluD and TruB, the protein is needed but not the product of the reaction it catalyzes+ Inhibition of 50S subunit assembly in both Dust and Tiny RluD-minus strains has also recently been observed (L+ Peil, N+ Gutgsell, J+ Ofengand, & J+ Remme, unpubl+ results)+ Considering all these results, a pattern begins to emerge in which rRNA modifying enzymes, at least the most common ones, ⌿ synthases and 29-O-methyltransferases, may have an assembly function in their own right, independent of their catalytic role in modified base formation+ In this regard, it is interesting to note the amino acid sequence homology between the N-terminus of RluD (residues 19-49) of this 326 amino acid protein with residues 10-40 of Hsp15, a protein highly induced by heat shock (Korber et al+, 1999)+ Hsp15 is a 133 amino acid protein that consists almost entirely of a new type of RNA-binding fold and which binds to 50S subunits carrying nascent protein chains with nanomolar affinity + In this context, the occurrence of pseudorevertants should be noted+ Such second-site mutants are found readily in the Dust strain, and pains must be taken to avoid them during subculturing+ They occur much more rarely in the Tiny strain, possibly because the grow...…”
Section: Discussionmentioning
confidence: 99%
“…E. coli yhbY is monocistronically transcribed, but it is adjacent to and divergently transcribed with ftsJ/rrmJ, which encodes a 23S rRNA methyl-transferase (Bugl et al 2000;Caldas et al 2000a). These genomic contexts motivated us to explore the possibility that E. coli YhbY functions in translation.…”
Section: E Coli Yhby Is Bound In Vivo To Precursors Of 50s Ribosomalmentioning
confidence: 99%
“…Although a ribosome lacking post-transcriptional modifications is able to synthesize peptides in vitro (Krzyzosiak et al 1987;Cunningham et al 1991;Green and Noller 1999;Khaitovich et al 1999), the conservation and clustering of modified nucleosides in functionally important regions of the ribosome suggest that they might be important for efficient translation, rRNA folding, ribosome assembly, or stability of ribosomes in vivo (Noller and Woese 1981;Brimacombe et al 1993;Ofengand and Fournier 1998;Decatur and Fournier 2002;Xu et al 2008). Indeed, several rRNA modifications have been shown to be important for 30S and 50S assembly and ribosome functioning (Igarashi et al 1981;Green and Noller 1996;Gustafsson and Persson 1998;Caldas et al 2000), and a number of additional modifications provide advantages under particular conditions, such as conferring resistance against ribosometargeting antibiotics (Cundliffe 1989;Weisblum 1995;Mann et al 2001;Toh et al 2008). However, the possible functional roles of the vast majority of modified nucleosides in rRNA remain unknown.…”
Section: Introductionmentioning
confidence: 99%